Aspects of health education with technology in basic input aspects of health in human education - R Destiwati; J Harahap (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2021)
The aspect of education in health must continue to be a part of concentration in various aspects which are an inseparable part by including things that contain technology so as to make an aspect of health easily understood and carried out by the community. The question in this article is the aspect of health education with technology in basic input aspects of health in human education. Which questions are answered in the method carried out by qualitative methods using various media. The results of the study found that aspects of health education with technology in basic input aspects of health in human education are carried out in various ways including technology and education, health and art, health and discipline aspects and health and learning